Evaluation of intestinal metaplasia associated with alkaline reflux gastritis and Helicobacter pylori in patients without gastric surgery (Annals of Medical Research, 2021)
None
Keywords: Duodenogastric Reflux; Metaplasia; Helicobacter Pylori.